Posttranscriptional control of the B cell receptor by HuR is essential for innate B cell maintenance and function - Dunja Capitan-Sobrino; Mailys Mouysset; Orlane Maloudi; Yann Aubert; Ines C. Osma-Garcia; Trang-My M. Nguyen; Greta Dunga; Maia Nestor-Martin; Virginie Mieulet; Manuel D. Diaz-Muñoz (Proceedings of the National Academy of Sciences, 2025)
Innate B-1 cells constitute a self-maintained layer of defense for early detection of bacteria, clearance of apoptotic cell debris, and removal of autoantigens driving autoimmunity. B-1 cells are originated from fetal tissues, but, as opposed to B-2 cells, the molecular mechanisms behind their development and homeostatic maintenance remain largely unknown. Here, we demonstrate that posttranscriptional regulation by the RNA binding protein HuR is essential for the homeostatic self-replenishment of innate B-1a cells, the expansion of B-1 cell clones targeting self-antigens, and the production of natural autoantibodies. HuR KO B-1 cells fail to express the high levels of surface B-cell receptor (BCR), TACI, and BAFFR required for tonic signaling and cell survival. At the molecular level, HuR promotes the translation of messenger RNAs encoding the IgM heavy chain and modules, in a direct or indirect manner, the expression of TACI and BAFFR. In summary, we reveal the need for posttranscriptional regulation in BCR expression, tonic signaling, and homeostatic maintenance of functional innate B-1 cells.